Method of providing wear-resistance of the blades of paddle mixers. - G. V. Petrishin; V. M. Bystrenkov; V. I. Odarchenko (Литьë и металлургия)
The work is devoted to solution of the actual problem to increase the service life of blade mixers used in the foundry industry. The existing methods for ensuring wear resistance of mixing blades are described, their advantages and disadvantages are indicated. Based on the analysis of scientific publications a technical solution for applying protective coatings to the blades of the mixer using gas-thermal spraying has been proposed. The results of laboratory studies of the wear rate of gas-thermal coatings from various powder mixtures of the Ni-Cr-B-Si system under conditions of abrasive wear are presented. The results of operational tests of experimental products under conditions of corrosion and abrasive wear during the operation of a paddle mixer are given. The composition of the powder mixtur ensuring maximum wear resistance of the mixer blades was developed.